2020
DOI: 10.3390/agronomy10111843
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Prediction of Rust Resistance in Tetraploid Wheat under Field and Controlled Environment Conditions

Abstract: Genomic selection can increase the rate of genetic gain in crops through accumulation of positive alleles and reduce phenotyping costs by shortening the breeding cycle time. We performed genomic prediction for resistance to wheat rusts in tetraploid wheat accessions using three cross-validation with the objective of predicting: (1) rust resistance when individuals are not tested in all environments/locations, (2) the performance of lines across years, and (3) adult plant resistance (APR) of lines with bivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…The application of genomic prediction depends on the population size, marker density, model performance, heritability of the trait, training population size, and breeding population relatedness ( Daetwyler et al, 2008 ; Bassi et al, 2016 ). In wheat, genomic prediction studies have been reported to predict rust resistance in diverse wheat landraces ( Daetwyler et al, 2014 ; Crossa et al, 2016 ), landraces from Afghanistan ( Tehseen et al, 2021 ), tetraploid wheat ( Azizinia et al, 2020 ), and improved wheat germplasm ( Ornella et al, 2012 ; Rutkoski et al, 2014 ; Bassi et al, 2016 ; Juliana et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The application of genomic prediction depends on the population size, marker density, model performance, heritability of the trait, training population size, and breeding population relatedness ( Daetwyler et al, 2008 ; Bassi et al, 2016 ). In wheat, genomic prediction studies have been reported to predict rust resistance in diverse wheat landraces ( Daetwyler et al, 2014 ; Crossa et al, 2016 ), landraces from Afghanistan ( Tehseen et al, 2021 ), tetraploid wheat ( Azizinia et al, 2020 ), and improved wheat germplasm ( Ornella et al, 2012 ; Rutkoski et al, 2014 ; Bassi et al, 2016 ; Juliana et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In all three models, the mean stripe rust prediction accuracies of the six Canadian spring wheat populations in the CV2 and CV0 scenarios varied from 0.54 to 0.84 (Table 2), which was greater than several other studies conducted on wheat. Previous GS studies conducted in non-Canadian wheat germplasm reported highly variable accuracies, which ranged from 0.39 to 0.56 in tetraploid wheat [37], from 0.16 to 0.72 in winter wheat [18][19][20]38], and from 0.12 to 0.79 in diverse spring wheat populations [17,18,21,39,40]. Overall, our results provided a strong justification for wheat breeders for integrating GS in developing stripe rust resistance spring wheat germplasm using the CV2 and/or CV0 scenarios regardless of the models and genetic background, which would reduce the cost, resources, and logistics associated with field evaluation by at least 25%.…”
Section: Discussionmentioning
confidence: 98%
“…This can invoke a strong discrepancy between the training population and selection candidates in the genomic prediction of disease resistance, since the phenotypic data of the training population does not reflect the current situation of the selection candidates if new virulent pathogen races occur in a given year of selection. Despite the presence of strong race dynamics, few genomic prediction studies distinguishing between race-nonspecific QDR and R-gene-mediated race-specific resistance for the wheat rusts (Rutkoski et al 2011(Rutkoski et al , 2015bJuliana et al 2017;Azizinia et al 2020). Focusing exclusively on the genetic improvement of QDR by using training and selection populations that were devoid of race-specific R-genes resulted thereby in some genetic gain for stem rust resistance in wheat (Rutkoski et al 2015b), while high prediction accuracies were observed in the presence of race-specific R-genes if they were effective in both the training population and the population of selection candidates (Juliana et al 2017;Azizinia et al 2020).…”
Section: Introductionmentioning
confidence: 99%